PENGARUH KONFORMITAS TEMAN SEBAYA TERHADAP PERILAKU MEMBOLOS PADA REMAJA SMKN 10 SEMARANG - Putri, Laksmita Ruwanda; Deliana, Sri Maryati; Rizki, Binta Mu'tiya (Intuisi : Jurnal Psikologi Ilmiah, 2017)
Abstract. Truant behavior is a form of teenager delinquency which is status offenses. This type of delinquency, it is a non-criminal delinquency type, but it has a quite big negative impact on teenagers. One of the factors that causing truant behavior is due to the influence of peer environment. This research aims to find out how much peers conformity influence teenagers’ truant behavior in SMKN 10 Semarang. This research is a quantitative research using regression analysis technique. Sample taking using the purposive sampling technique. The samples in this research are 233 students. Measuring instruments in this research used two scales that are peers conformity scale and truant behavior scale. The research result shows that the correlation coef icient (R) between peers conformity on teenagers’ truant behavior amounted to 0. 0,591 with a determination coef icient (R Square) of 0.349 and F count equal to 123,848 with a significance level of 0.00 <0.05, it indicates that the variable peers conformity has a significant positive ef ect on the variable of truant behavior by 34,9% while the rest is influenced by other factors. The higher the influence of peers conformity, then the higher the teenagers’ truant behavior of SMKN 10 Semarang, conversely, the lower the influence of peers conformity, then the lower the teenagers’ truant behavior of SMKN 10 Semarang. Peers conformity is in the middle category with the most contributing aspect is the normative influence aspect. Truant behavior is in the low category with the most contributing aspect is the absent from school for a full day aspect.